ChemInform Abstract: One‐Pot Solid Phase Synthesis of (E)‐Nitroalkenes. Issue 3 (21st January 2014) - Rokhum, Lalthazuala; Bez, Ghanashyam
Abstract An efficient one‐pot protocol for the synthesis of (E)‐nitroalkenes by reaction of aldehydes and nitroalkanes in the presence of polymer‐bound triphenylphosphine, iodine, and imidazole is described.